Signal Processing for Fault Detection and Diagnosis in Electric Machines and Systems - Benbouzid, Mohamed (Energy Engineering., 2020)
This book contains 5 chapters that discusses the following topics: Parametric signal processing approach; The signal demodulation techniques; Kullback-Leibler divergence for incipient fault diagnosis; Higher-order spectra and Fault detection and diagnosis based on principal component analysis.